Genome-Wide Linkage Analysis to Identify Genetic Modifiers of ALK Mutation Penetrance in Familial Neuroblastoma - Devoto, Marcella (S. Karger AG, 2011)
BACKGROUND: Neuroblastoma (NB) is an important childhood cancer with a strong genetic component related to disease susceptibility. Approximately 1% of NB cases have a positive family history. Following a genome-wide linkage analysis and sequencing of candidate genes in the critical region, we identified ALK as the major familial NB gene. Dominant mutations in ALK are found in more than 50% of familial NB cases. However, in the families used for the linkage study, only about 50% of carriers of ALK mutations are affected by NB. METHODS: To test whether genetic variation may explain the reduced penetrance of the disease phenotype, we analyzed genome-wide genotype data in ALK mutation-positive families using a model-based linkage approach with different liability classes for carriers and non-carriers of ALK mutations. RESULTS: The region with the highest LOD score was located at chromosome 2p23–p24 and included the ALK locus under models of dominant and recessive inheritance. CONCLUSIONS: This finding suggests that variants in the non-mutated ALK gene or another gene linked to it may affect penetrance of the ALK mutations and risk of developing NB in familial cases.